Interactions of hyaluronic Acid with the skin and implications for the dermal delivery of biomacromolecules - Witting, Madeleine; Boreham, Alexander; Brodwolf, Robert; Vávrová, Kateřina; Alexiev, Ulrike; Friess, Wolfgang; Hedtrich, Sarah (Molecular pharmaceutics, 2015)
Hyaluronic acid (HA) hydrogels are interesting delivery systems for topical applications. Besides moisturizing the skin and improving wound healing, HA facilitates topical drug absorption and is highly compatible with labile biomacromolecules. Hence, in this study we investigated the influence of HA hydrogels with different molecular weights (5 kDa, 100 kDa, 1 MDa) on the skin absorption of the model protein bovine serum albumin (BSA) using fluorescence lifetime imaging microscopy (FLIM). To elucidate the interactions of HA with the stratum corneum and the skin absorption of HA itself, we combined FLIM and Fourier-transform infrared (FTIR) spectroscopy. Our results revealed distinct formulation and skin-dependent effects. In barrier deficient (tape-stripped) skin, BSA alone penetrated into dermal layers. When BSA and HA were applied together, however, penetration was restricted to the epidermis. In normal skin, penetration enhancement of BSA into the epidermis was observed when applying low molecular weight HA (5 kDa). Fluorescence resonance energy transfer analysis indicated close interactions between HA and BSA under these conditions. FTIR spectroscopic analysis of HA interactions with stratum corneum constituents showed an α-helix to β-sheet interconversion of keratin in the stratum corneum, increased skin hydration, and intense interactions between 100 kDa HA and the skin lipids resulting in a more disordered arrangement of the latter. In conclusion, HA hydrogels restricted the delivery of biomacromolecules to the stratum corneum and viable epidermis in barrier deficient skin, and therefore seem to be potential topical drug vehicles. In contrast, HA acted as an enhancer for delivery in normal skin, probably mediated by a combination of cotransport, increased skin hydration, and modifications of the stratum corneum properties.
Keywords: Cattle; Animals; skot; FTIR; FLIM; In Vitro Techniques; aplikace kožní; Skin Absorption; techniky in vitro; sérový albumin hovězí; Administration, Cutaneous; Serum Albumin, Bovine; Spectroscopy, Fourier Transform Infrared; prasata; kůže; kyselina hyaluronová; kožní absorpce; proteins; Hyaluronic Acid; spektroskopie infračervená s Fourierovou transformací; Skin; Swine; epidermal drug delivery; skin penetration; skin hydration; hyaluronic acid; zvířata